Autovaccine immunoprophylaxis in patients with neurogenic bladder experiencing recurrent urinary tract infections - Bonillo-García, Miguel Ángel; Ordaz-Jurado, Domingo Guzmán; Ortiz-Salvador, Juan; Colet-Guitert, Josep Oriol; Morán-Pascual, Eduardo; Martínez-Cuenca, Esther; Arlandis-Guzmán, Salvador (Frontiers in Immunology, 2025)
IntroductionNeurogenic Bladder (NB) patients are highly susceptible to recurrent urinary tract infections (UTIs), often requiring repeated hospitalizations and prolonged antibiotic use. Current preventive strategies, including long-term antibiotics, frequently fail due to resistance and limited efficacy. Autovaccination, a form of personalized immunoprophylaxis using inactivated patient-specific bacterial strains, has shown potential in reducing UTI recurrence but has not been well studied in NB populations.MethodsA prospective, single-center study was conducted at the Hospital Universitari i Politécnic La Fe València, Spain. Eligible participants were individuals of any gender, aged between 18 and 65 years, with a confirmed diagnosis of NB. They were required to have experienced recurrent UTIs within the past twelve months, despite having undergone a six-month regimen of prophylactic antibiotics without success. Participants received a sublingual bacterial autovaccine (Uromune®) prepared from uropathogens isolated from their own urine cultures. Primary outcomes included changes in hospitalization and emergency admission rates, while secondary outcomes assessed UTI-free time and patient-reported outcomes using validated instruments.ResultsThe study included 71 adult NB patients with recurrent UTIs. Autovaccination significantly reduced hospitalizations (from 1.76 ± 3.47 to 0.78 ± 1.38, p < 0.001) and emergency admissions (from 8.62 ± 6.35 to 3.93 ± 4.48, p < 0.001). At 3, 6, 9, and 12 months post-treatment, UTI-free rates were 69.1%, 42.6%, 29.4%, and 20.6%, respectively. Most patients reported high satisfaction and perceived clinical improvement.ConclusionsAutovaccination appears to be a promising strategy for reducing the burden of recurrent UTIs in NB patients, with high patient satisfaction and fewer hospital visits. These findings support the need for larger, multicenter trials to confirm efficacy and define optimal treatment protocols.